The Immunopathophysiology of Endometriosis. Issue 9 (September 2018) - Symons, Lindsey K.; Miller, Jessica E.; Kay, Vanessa R.; Marks, Ryan M.; Liblik, Kiera; Koti, Madhuri; Tayade, Chandrakant
Abstract : Endometriosis is a chronic, inflammatory, estrogen-dependent disease characterized by the growth of endometrial tissue outside of the uterine cavity. Although the etiology of endometriosis remains elusive, immunological dysfunction has been proposed as a critical facilitator of ectopic lesion growth following retrograde menstruation of endometrial debris. However, it is not clear whether this immune dysfunction is a cause or consequence of endometriosis. Thus, here we provide in-depth insights into our current understanding of the immunopathophysiology of endometriosis and highlight challenges and opportunities for future research. With the explosion of successful immune-based therapies targeting various chronic inflammatory conditions, it is crucial to determine whether immune dysfunction can be therapeutically targeted in endometriosis. Highlights: Immunological dysfunction, involving defective immunosurveillance against autologous tissue deposited in the peritoneal cavity, facilitates endometriotic lesion growth in endometriosis patients and ultimately perpetuates disease symptoms. Conversely, innate and adaptive immune cells from endometriosis patients produce several proinflammatory and blood vessel growth-promoting factors that contribute to hallmarks of disease pathophysiology. Persistent and prolonged endometriosis-associated inflammation further contributes to comorbidities. Recent studies suggest that endometriotic lesions harbor a unique microenvironment. The interplay between immune cells with stromal and epithelial compartments of lesions is regulated by hormonal pathways. Targeting dysregulated immune pathways represents a potential avenue for novel therapeutic development that will hopefully not impact fertility.